Pelvic Drop Changes due to Proximal Muscle Strengthening Depend on Foot-Ankle Varus Alignment - Aline de Castro Cruz; Sérgio Teixeira Fonseca; Vanessa Lara Araújo; Diego da Silva Carvalho; Leonardo Drumond Barsante; Valéria Andrade Pinto; Thales Rezende Souza (Applied Bionics and Biomechanics)
Background. Strengthening of hip and trunk muscles can modify pelvis and hip movements. However, the varus alignment of the foot-ankle complex (FAC) may influence the effects of muscle strengthening, due to the relationship of FAC alignment with pelvic and hip kinematics. This study evaluated the effects of hip and trunk muscle strengthening on pelvis and hip kinematics during walking, in subgroups with larger and smaller values of FAC varus alignment. In addition, this study evaluated the effects of hip and trunk muscle strengthening on hip passive and active properties, in the same subgroups. Methods. Fifty-three women, who were divided into intervention and control groups, participated in this nonrandomized controlled trial. Each group was split into two subgroups with larger and smaller values of FAC varus alignment. Hip and trunk muscle strengthening was performed three times a week for two months, with a load of 70% to 80% of one repetition maximum. Before and after strengthening, we evaluated (1) pelvis and hip excursions in the frontal and transverse planes during walking, (2) isokinetic hip passive external rotator torque, and (3) isokinetic concentric and eccentric peak torques of the hip external rotator muscles. Mixed analyses of variance (ANOVAs) were carried out for each dependent variable related to walking kinematics and isokinetic measurements (α=0.05). Results. The subgroup with smaller varus alignment, of the intervention group, presented a reduction in pelvic drop after strengthening (P=0.03). The subgroup with larger varus alignment increased pelvic drop after strengthening, with a marginal significance (P=0.06). The other kinematic excursions did not change (pelvic anterior rotation P=0.30, hip internal rotation P=0.54, and hip adduction P=0.43). The intervention group showed increases in passive torque (P=0.002), peak concentric torque (P<0.001), and peak eccentric torque (P<0.001), independently of FAC alignment. These results suggest that FAC varus alignment influences the effects of strengthening and should be considered when hip and trunk muscle strengthening is used to reduce pelvic drop during walking.